Desain Album “Collide” Band Dieonic - Muhammad Akhdan Sytra; Defrizal Saputra (Lembaga Pengembangan Kinerja Dosen, 2024)
Dieonic is an Alternative Rock music group with the Shoegaze subgenre hailing from Padang, Indonesia. Formed in 2022, Dieonic presents a fusion of key shoegaze elements within a series of alternative rock tracks, refining the essence of emo music. In the midst of Padang's vibrant underground music scene, Dieonic emerges with a distinctive sound, deviating from the conventional trends. This latest project aims to develop a visual communication concept that mirrors the artistic visualization of Dieonic's musical creations and their unique identity. Beyond offering educational insights into the significance of album design in the music industry, this endeavor concentrates on fortifying Dieonic's visual branding as a pivotal aspect of the band's identity, employing a semiotic approach. The cover design for Dieonic's 'Collide' album underwent a meticulous process, utilizing the 5W+1H analysis and the 4D method design for data analysis. The subsequent creative design seeks to encapsulate the band's essence. The resulting design serves as the primary medium in the form of the album itself, accompanied by supplementary materials such as album CDs, booklets, Spotify previews, posters, t-shirts, and flags. These diverse media will undergo thorough testing for their efficacy with a verified target audience to gauge their overall success.